Strategie translatorskie w rosyjskich tłumaczeniach utwo rów Bolesława Leśmiana - Ostrowska, Alona (Przegląd Rusycystyczny, 2008)
TRANSLATION STRATEGIES OF RUSSIAN TRANSLATION OF BOLESŁAW LEŚMIAN’S POEMS Summary Analyzing series of translations the author of the article, is trying to answer questions — which translation strategies are used by men- and which — by women-translator; does female style of writing infl uence the quality of translations.As a result of analysis it turned out that Maria Petrovykh, Natalia Astafi eva would often use adjective amplifi cations and added pronouns and conjunctions to complete verses. They also made their translations more expressive. Gennady Zeldowich chose completely another tactic. His translations are utterly different from female ones. They are concise and have more neologisms. ПЕРЕВОДЧЕСКИЕ СТРАТЕГИИ В ПЕРЕВОДАХ ПРОИЗВЕДЕНИЙ БОЛЕСЛАВА ЛЕСЬМЯНА НА РУССКИЙ ЯЗЫК Резюме Автор статьи, анализируя серии переводов стихов Болеслава Лесьмяна, старается ответить на вопросы — какими определенными переводческими стратегиями поль-зуются переводчики, а какими — переводчицы; можно ли говорить о влиянии женского стиля на качество перевода.В результате анализа оказывается, что Мария Петровых и Наталья Астафьева при бегают к прилагательной амплификации, заполняют размер стиха союзами, местоимениями, повышают эксрессию перевода. Геннадий Зельдович выбирает совершенно другую тактику. Его перевод отличается от переводов женщин лапидарностью, свежестью, большим количеством языковых инноваций.